Development of Interactive Digital Motion Graphic Media Assisted by Edpuzzle on Volcanism Material - Iqbal Dio Ardiansyah; Tuti Mutia; Yusuf Suharto; Bagus Setia Budi Wihoho (Future Space: Studies in Geo-Education, 2025)
The dynamic development of the times in general provides changes to aspects of education that are increasingly integrated with technology. The utilization of technology in the education sector creates various conveniences and the availability of learning media to increase the effectiveness of learning. Based on the results of the needs analysis conducted at MA Bilingual Batu City, it was found that students need renewal of learning media that can illustrate material volcanism that is difficult to reach. This research aims to develop media that can help students' understanding and see its feasibility and practicality. This research uses the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). By using visual motion graphic media, students can clearly see the phenomenon of volcanism that occurs. The results of this study showed a media validation test of 98.3% and a material validation test of 77.5%. In the teacher test, the score was 100% and the student test was 90.6%. Based on the results of the analysis, it can be said that this media is suitable for implementation in geography learning.